2009
DOI: 10.1111/j.1468-2982.2008.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Ictal and Interictal Phonophobia in Migraine—A Quantitative Controlled Study

Abstract: The aim of the study was to evaluate quantitatively ictal and interictal phonophobia in episodic migraine (EM). We included subjects with EM and age-and gender-matched controls. Sound stimuli were pure tones at frequencies of 1000, 4000 and 8000 Hz. Sound aversion thresholds (SATs) were determined as the minimal sound intensity perceived as unpleasant or painful. Migraineurs were examined both between and during attacks. We compared interictal SATs in migraineurs with those in controls. We also compared ictal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 16 publications
6
67
2
Order By: Relevance
“…The interictal sound aversion threshold for 1000, 4000, and 8000 Hz stimulation was significantly lower than that of controls and decreased further during ictal migraine (Ashkenazi et al, 2009). BAEPs are altered in migraine, especially the later PL5 and IPL P1 to P5 (Bussone et al, 1985;Firat et al, 2006;Kochar et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The interictal sound aversion threshold for 1000, 4000, and 8000 Hz stimulation was significantly lower than that of controls and decreased further during ictal migraine (Ashkenazi et al, 2009). BAEPs are altered in migraine, especially the later PL5 and IPL P1 to P5 (Bussone et al, 1985;Firat et al, 2006;Kochar et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Auditory symptoms are prominent in migraine and are the focus of this study; they include fluctuating low-frequency hearing loss, sudden deafness, auditory hallucinations, tinnitus, and phonophobia. Significant phonophobia is often found in interictal migraine and worsened during ictal migraine compared to controls (Ashkenazi et al, 2009;Vingen et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous allodynia is believed to be related to abnormal modulation of descending pain signals (Bingel and Tracey, 2008, Moulton et al, 2008). Although these hypersensitivities are magnified during the ictal phase of migraine (Bigal et al, 2008, Kelman, 2004, Lipton et al, 2008, Russell et al, 1996, Wober-Bingol et al, 2004) these hypersensitivities can also persist during the interictal phase of migraine (Ashkenazi et al, 2009, Main et al, 1997, Schwedt et al, 2011, Schwedt et al, 2015), when patients are pain-free. Several studies have shown that migraine patients demonstrate hypersensitivities during the interictal phase including lower thresholds to heat-induced pain (Schwedt et al, 2015), higher sensitivity to touch and light using self-report questionnaires (Chen et al, 2015, Cucchiara et al, 2014, Lovati et al, 2008), and altered functional brain activation patterns to painful heat stimuli (Chen et al, 2015, Schwedt et al, 2014a, Schwedt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[19] Quantitative testing shows that the interictal migraineur is more sensitive to sound compared to the non-migraine control and that the migraine patient is even more sensitive to sound during a migraine attack compared to the interictal period. [14, 1920]…”
Section: Aberrant Unisensory Processing In Migrainementioning
confidence: 99%